Olfaction in Primary Atrophic Rhinitis and Effect of Treatment - Anupam Mishra MBBS, MS, DNB; Nimisha Mishra Shukla MBBS, MD; Veerendra Verma MBBS, MS; Subhash Chandra Mishra MBBS, MS, DLO (OTO Open, 2020)
Objective To assess olfactory and clinical morbidity in primary (idiopathic)–type atrophic rhinitis and its course following treatment. Study Design Prospective nonrandomized controlled cohort study with follow-up. Setting Department of Otorhinolaryngology and Head and Neck Surgery of a university hospital (tertiary heath care center). Methods Sixty-one patients with atrophic rhinitis underwent assessment of clinical severity with baseline olfaction with the Brief Smell Identification test, while the improvement of their status following surgical versus nonsurgical treatment was further assessed. Results Olfaction was universally deranged with bimodal age presentation and female predominance (61%). Clinical improvement was significantly associated with surgical treatment but did not reveal any relation with up-front severity of disease. A near-significant association of age with severity did not reveal significance when stratified by age group. Baseline olfaction or its change following treatment did not reveal any significance with severity of disease or clinical improvement. Radiologic atrophy also did not reveal any significant relation with severity criteria. Conclusions Olfactory functions as compared with clinical parameters provided better reflection of underlying (systemic) pathology with environmental interaction, while later it mainly signified localized condition. Accordingly, olfaction was affected early and recovered slowly (or not at all), independent of clinical morbidity, which in turn is affected rather late but recovers early. Olfactory dysfunction at the initial stage may be a surrogate marker of potential worsening clinical condition, since bacteria often superinfect underlying susceptible nasal environment. While surgery mainly improved clinical parameters without affecting olfaction directly, a true improvement would include recovery of both.